2019
DOI: 10.1007/s42764-019-00006-6
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-associated genomic instability in cancer

Abstract: Inflammation is essential in protecting us against foreign pathogens. However when left unchecked, it becomes chronic inflammation, a potential precursor to carcinogenesis. While inflammatory signalling provides pro-survival stimuli, it also causes genomic instability and allows mutant cells to escape cell cycle arrest and apoptosis. This occurs through the release of reactive oxygen/nitrogen species (ROS/RNS), the increased expression of activation-induced cytidine deaminase (AID), inhibition of p53 function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Several biological mechanisms may explain the associations between the analytes studied here and risk of postmenopausal breast cancer. An inflammatory microenvironment has been directly linked to various processes including oxidative stress, DNA damage and genomic instability which have been associated with the initiation of cancer 37,38 . Moreover, most postmenopausal breast tumors are estrogen‐sensitive, and, importantly, some studies have found that inflammation is associated with processes that lead to increased estrogen signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Several biological mechanisms may explain the associations between the analytes studied here and risk of postmenopausal breast cancer. An inflammatory microenvironment has been directly linked to various processes including oxidative stress, DNA damage and genomic instability which have been associated with the initiation of cancer 37,38 . Moreover, most postmenopausal breast tumors are estrogen‐sensitive, and, importantly, some studies have found that inflammation is associated with processes that lead to increased estrogen signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The main inflammatory pathways include the non-canonical and canonical NF-κB, JAK-STAT and MAPK signaling pathways. Activation of each or combined pathways eventually drives abnormal gene transcription that has been implicated in cancer development (Pua et al 2019). Even though no evidence showed a direct role of NF-κB signaling in gastric cancer stem cells, aberrant activation of the pathway contributes to increased proliferation and evasion of apoptosis, which could contribute to tumorigenesis (Kang et al 2008;Liu et al 2004).…”
Section: Helicobacter Pylori Infection Induces Inflammation and Oxidamentioning
confidence: 99%
“…ROS production has been observed in patients and cultured cells infected with H. pylori (Davies et al 1994;Drake et al 1998). The sustained release of ROS/ RNS together with other risk factors including increased activation-induced cytidine deaminase (AID), inhibited p53 and reactivated TERT expression contribute to DNA damage and genomic instability during chronic inflammation (Pua et al 2019).…”
Section: Helicobacter Pylori Infection Induces Inflammation and Oxidamentioning
confidence: 99%
“…According to previous studies [16][17][18][19][20], mediators produced by activated in ammatory cells promote a variety of damages, including genetic mutations, post-translational modi cation of proteins involved in apoptosis, DNA repair, cell cycle control and signal transduction, as well as DNA and histone methylation, generating a pathologically conducive microenvironment which may induce the growth and progression of malignancies. Several previous studies suggested that chronic antigenic stimulation, together with oncogenic events such as p53 inactivation and K-ras mutation in IgG4-RD led to an increased risk of malignant transformation compared with the general population [6,21].…”
Section: Discussionmentioning
confidence: 99%